STUDI ATAS PENENTUAN RUANG LINGKUP PENGUJIAN SUBSTANTIF BERDASARKAN EVALUASI PENGENDALIAN UMUM DAN APLIKASI (Kasus Siklus Penjualan Voucher Telepon Pada CV S) - Elizabeth Tiur Manurung; Elvira Yapi (Center for Economic Studies Universitas Katolik Parahyangan, 2014)
The purpose of this study is to determine the scope of substantive test in order to audit sales cycle. With using descriptive analytical method, this research come up to conclusion that the company has implemented a satisfied general control and application control. The company has applied all components that will increase control in sales cycle by using software accurate version 3, such as keeping up IT administration, developing system, segregation of IT function, secure control for safeguarding assets and on line, backup procedure. For application control, the company has applied control like validation test for input such as field check, sign check, size check,completeness check and prenumbered document has used in sales cycle. Especially for sales oreder, the cashier have to sign three copies to reach good control. Substantive test of transaction determined by the result of evaluation of General controls and application controls that resulted in satistfying controls, so then audit nature can use test of control, audit timing is interim, and the evidence extent will be smaller as possible